2017
DOI: 10.4274/jcrpe.3817
|View full text |Cite
|
Sign up to set email alerts
|

Basal Serum Neurokinin B Levels in Differentiating Idiopathic Central Precocious Puberty from Premature Thelarche

Abstract: Objective:To find out the diagnostic role of kisspeptin and neurokinin B in idiopathic central precocious puberty (ICPP) and premature thelarche (PT).Methods:The girls who presented with early breast development before the age of 8 years were evaluated. Patients with intracranial pathologies were excluded. Basal and stimulated follicle-stimulating hormone/luteinizing hormone (LH) levels and basal neurokinin B/kisspeptin levels were measured. Patients who had peak value of LH >5 mIU/mL and a bone age (BA)/chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 20 publications
4
10
0
Order By: Relevance
“…Although the method is highly sensitive, its specificity is low (94.1% sensitivity and 60.7% specificity), which limits its use as a single diagnostic tool until further data can be obtained from conducting larger studies. Perhaps an improvement to diagnosis can be achieved by incorporating measurements for another metabolite, such as serum levels of neurokinin B ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the method is highly sensitive, its specificity is low (94.1% sensitivity and 60.7% specificity), which limits its use as a single diagnostic tool until further data can be obtained from conducting larger studies. Perhaps an improvement to diagnosis can be achieved by incorporating measurements for another metabolite, such as serum levels of neurokinin B ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Using a systematic review and meta-analysis, we compared the KP levels between 316 girls with CPP and 251 controls from 11 studies (Table 1) [20,[34][35][36][37][38][39][40][41][42][43]. In all studies, the values of KP concentration were higher in CPP girls than in controls (SMD = 1.53; CI 95% = 0.56-2.51), except in 1 study [42] which found no difference in KP levels.…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed poor descriptions of the sample collection and pre-analytical procedures. The description of the healthy controls presented mixed results with 5 studies presenting limited descriptions [20,34,36,40,41]. However, the case group characteristics, description, and diagnostic criteria presented generally better descriptions.…”
Section: Quality Assessmentmentioning
confidence: 92%
See 2 more Smart Citations